Valorization of Phenolic and Carotenoid Compounds of Sechium edule (Jacq. Swartz) Leaves: Comparison between Conventional, Ultrasound- and Microwave-Assisted Extraction Approaches - Vieira, EF (2022)
Chayote leaves are known for culinary and traditional medicine applications. This work intended to recover carotenoids and phenolic compounds from chayote leaves using the ultrasound-assisted extraction (UAE). A Box–Behnken design was employed to investigate the impact of extraction time, temperature, and ultrasonic power on the recovery of total carotenoids, total phenolic compounds, and antioxidant activities. For comparative purposes, chayote leaf extracts were prepared by maceration (ME) and microwave-assisted extraction (MAE), using the same time and temperature conditions optimized by UAE. Extraction at 50 °C and 170 Watts for 30 min provided the optimal UAE conditions. UAE showed better extraction efficacy than ME and MAE. The HPLC analysis of the extracts showed that the xanthophyll class was the main class of carotenoids, which constituted 42–85% of the total carotenoid content, followed by β-carotene and tocopherol. Moreover, 26 compounds, classified as phenolic acids, flavonols, flavonoids and other polar compounds, were identified in the chayote leaf extracts. Flavonols accounted for 55% of the total compounds quantified (the major compound was myricetin) and phenolic acids represented around 35%, mostly represented by ferulic acid, chlorogenic acid and (+)-catechin. This study revealed the potential of UAE as an effective green extraction technique to recover bioactive compounds from chayote leaves, for food, and for pharmaceutical and cosmetic applications.